Piperazine as Leaving Group in A3 Adducts: Fast Access to Alkynyl Indoles - Kerim, Mansour Dolè; El Kaïm, Laurent (Synlett, 2016)
The A3 coupling between N-ethylpiperazine and electron-rich aromatic aldehydes forms adducts that may be easily used as electrophiles towards electron-rich heterocycles such as indoles. The removal of the piperazine moiety is triggered by the addition of 1,2-dibromoethane. Overall, the reaction provides efficient access to alkynyl indoles and pyrroles.
Keywords: A3 reaction; alkyne; piperazine; indoles